ANALYZING METHODS OF ASSESSING SOCIAL AND ECONOMIC EFFICIENCY OF SPORTS CENTERS IN RUSSIAN UNIVERSITIES - Petr A. Solovev (Вестник Российского экономического университета имени Г. В. Плеханова, 2019)
The article studies factors affecting seriously the profitability of sports centers. The author designed a system of indicators, which can help assess their social and economic efficiency. It is shown that achievement of high figures of social and economic efficiency of sports infrastructure functioning is possible only by using effective managerial tools. Effectiveness can be estimated by comparison of the obtained effect of a certain type of activity with raised resources. Specificity of the proposed system of indicators is its potential to estimate the efficiency of the current sports centers’ work and at the same time to find negative factors influencing their functioning. Indicators proposed by the author can be used in complex appraisal of centers’ work. The information collected with their help can help identify drawbacks in their operation and, consequently take adequate managerial decisions. In order to analyze satisfaction with services of the sp[orts center it is proposed to use a questionnaire. On the basis of the survey results a formula of assessing the general satisfaction of clients was put forward. The recommended indicators can be used in the complex appraisal of the sports center work.